Discurso de ódio, constituição subjetiva e alteridade: reflexões a partir da psicanálise - Feitoza, Sarah Dáleth Andrade Lemes (2024)
The general objective of the research is to discuss hate speech, understanding it through subjective constitution and social ties, based on Lacanian psychoanalysis, considering the field of otherness. The specific objectives are: first, to establish the psychoanalytic conception of the subject; subsequently, to examine the field of otherness as a founding element of the subject's constitution; and finally, to elaborate on what can be understood about hate speech, since, from a Lacanian perspective, discourse is what integrates the subject into the social bond. Each of the specific objectives constitutes a chapter of the dissertation. This research is configured as a theoretical inquiry in psychoanalysis. In this sense, it is a qualitative research, fundamentally based on bibliographic procedures and exploratory regarding its objectives. It aims to utilize the theoretical assumptions of Lacanian psychoanalysis, wherein the subject is constituted as an effect of language, at the intersection between the unconscious and drives. The unconscious, structured as a language, operates through metaphors and metonymies, with representations invested libidinally, highlighting the topical, economic, and dynamic nature of the unconscious. This subject is not constituted apart from language, culture, and the social environment, and therefore, it can be categorically stated that there is no subjective constitution outside the field of otherness. Civilization, however, is founded on a considerable amount of drive renunciation, which generates malaise. Around this malaise, discourses are created to contain it. These discourses establish social bonds. However, due to the brutal mode of capitalism in which we live today, this logic has been subverted, and discourses no longer generate social bonds; instead, they undermine them. In this sense, hate speech seems to contain some similarity to the structure of the Discourse of Markets, as postulated by Lacan